Cognitive Barriers in Reconstructing the Concepts of Squares and Triangles Among Adventitiously Blind Students - Siti Mutmainah; Mega Suliani (Journal of Research in Science and Mathematics Education, 2026)
Purpose: Geometric concept reconstruction requires learners to identify, integrate, and verify defining attributes of shapes within coherent conceptual structures. For adventitiously blind students, this process is particularly complex because prior visual experiences must be coordinated with tactile information obtained after vision loss. Methodology: This exploratory single-case study aimed to analyze the cognitive barriers experienced by an adventitiously blind junior high school student in reconstructing the concepts of squares and triangles through tactile manipulation. Data were collected through concept reconstruction tasks using wooden sticks, observations of tactile exploration, photographic documentation, and semi-structured interviews. The data were analyzed using thematic coding supported by triangulation across observation, interview, and documentation sources. Findings: The findings showed that the participant identified geometric figures primarily based on the number of sides. Although the triangle was reconstructed as a closed figure, the square reconstruction did not fully satisfy formal geometric properties because closure, side relationships, and overall regularity were not consistently coordinated. Three interrelated cognitive barriers emerged: geometric attribute integration, representational translation, and geometric verification. Significance: These barriers appeared to form an interconnected sequence within the participant's tactile concept reconstruction process. The findings suggest that geometry instruction for adventitiously blind learners should provide explicit scaffolding for integrating attributes, translating conceptual knowledge into tactile actions, and verifying geometric structures holistically.